2020
DOI: 10.1016/j.tsf.2019.137736
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer passive radiative selective cooling coating based on Al/SiO2/SiNx/SiO2/TiO2/SiO2 prepared by dc magnetron sputtering

Abstract: A multilayer passive radiative selective cooling coating based onAl/SiO2/SiNx/SiO2/TiO2/SiO2 prepared by dc magnetron sputtering is presented. The design was first theoretically optimized using the optical constants, refractive index and extinction coefficient of thin single layers. The spectral optical constants in the wavelength range from 0.3 to 27 µm were calculated from the transmittance and reflectance data of thin single layers deposited on silicon and glass substrates. The samples were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…[8] Moreover, Titanium dioxide (TiO 2 ) has attracted lots of interest recently. The transparent window of TiO 2 covers from 8 to 13 μm, [167,168] and its band gap is relatively high at 3.2 eV. [166] The propagation losses of TiO 2 strip waveguides could achieve 2.2 dB cm −1 at 1.55 μm.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…[8] Moreover, Titanium dioxide (TiO 2 ) has attracted lots of interest recently. The transparent window of TiO 2 covers from 8 to 13 μm, [167,168] and its band gap is relatively high at 3.2 eV. [166] The propagation losses of TiO 2 strip waveguides could achieve 2.2 dB cm −1 at 1.55 μm.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…The silver layer was firstly deposited on the silicon wafer by using dc magnetron sputtering, and then layers of Si 3 N 4 and SiO 2 were deposited. [39] After that, an array of grooves on the top of the SiO 2 layer could be fabricated with lithography and the inductively coupled plasma reactive ion etching method. [40] A sacrificial layer was deposited on the silica layer to obtain the triangular prism patterns through the lithography and wetetching process.…”
Section: Model Designmentioning
confidence: 99%
“…This method worked as a linear regression applied to spatial sample data which was used as regressor, Z(s), in order to predict a dependent variable, Z(s 0 ), at a given location (7). The weight given by the model to each of the points in the sample was determined by a variogram function (8)…”
Section: Interpolation Kriging Modelmentioning
confidence: 99%
“…In 2014, Raman et al [6] demonstrated a temperature drop-4-5 • C-below ambient under direct sunlight in photonic radiative cooling, which combined layers of SiO 2 and HfO 2 on top of a silver surface. The recent development of new multilayer thin structures [6][7][8], porous polymers [9][10][11], nanoparticle materials [12], metamaterials [13][14][15][16] and photonic crystals [17][18][19], allows the manufacture of selective surfaces which emit only in the 8-14 µm range while reflecting the incoming solar radiation.…”
Section: Introductionmentioning
confidence: 99%